2022
DOI: 10.1002/pat.5692
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of environmental stress cracking performance, load‐carrying capacity, and UV light barrier property of polyethylene terephthalate packaging material

Abstract: This study deals with the improvement of light barrier properties and stress cracking strength of polyethylene terephthalate (PET) packaging materials by incorporating calcium metaborate (CaB 2 O 4 ). CaB 2 O 4 powders were synthesized by the sol-gel method. After the extrusion process produced PET/ CaB 2 O 4 granules, the preform and bottle production was carried out by injection molding and blow molding. Compared to pure PET, UV transmittance is reduced (~88%), and it is more effective at lower wavelengths (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(91 reference statements)
2
6
0
Order By: Relevance
“…In this work, the incorporation of CaO resulted in PET chains that were shorter and had more COOH decomposition. Similarly, previous investigations have shown that usage of inorganic additives CaB 2 O 4 and Ca 3 B 2 O 6 promoted COOH degradation. On the contrary, COOH degradation tended to decrease in a study when Mg 2 B 2 O 5 was added to PET.…”
Section: Results and Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this work, the incorporation of CaO resulted in PET chains that were shorter and had more COOH decomposition. Similarly, previous investigations have shown that usage of inorganic additives CaB 2 O 4 and Ca 3 B 2 O 6 promoted COOH degradation. On the contrary, COOH degradation tended to decrease in a study when Mg 2 B 2 O 5 was added to PET.…”
Section: Results and Discussionsupporting
confidence: 70%
“…For carbonated beverages, it is desirable to use packages that can withstand 5 bar of internal pressure at room temperature. The characteristics of PET packaging materials are critical both for preservation of taste, smell, and nutritional values of foods and for consumer health and safety. , In addition to the aforementioned requirements, research studies are also ongoing to enhance UV permeability, gas barrier, and chemical migration properties of PET composites. For instance, to stop food in PET bottles exposed to sunlight from degrading as a result of a photochemical reaction, several additives are added to the PET body. , …”
Section: Introductionmentioning
confidence: 99%
“…As a result of the increase in crystallinity, UV light transmittance decreased. In addition, this can be attributed to the ability of borate particles to absorb high‐energy light effectively 42 . The lowest UV transmittance was achieved at the incorporation of 0.8% Ca 3 B 2 O 6 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this can be attributed to the ability of borate particles to absorb high-energy light effectively. 42 The lowest UV transmittance was achieved at the incorporation of 0.8% Ca 3 B 2 O 6 . It is noteworthy that the UV transmittance tends to increase slightly for all additive ratios when the wavelength increases from 400 to 700 nm.…”
Section: Uv Light Transmittance Of Pet Compositesmentioning
confidence: 95%
“…Akkurt et al [ 7 ] used Taguchi method (TM), Grey Relational Analysis (GRA), and ECHIP to analyze the effects of preform temperature, stretching rod position, and final pressure, and optimized the performance parameters. In addition, the orientation and crystallinity of PET molecules are also the main factors that determine whether the mechanical properties of finished products are excellent [ 8 , 9 , 10 ]. Demirel et al [ 11 ] used PET/nano hydroxyapatite (nHAp) composite particles to produce PET/nHAp bottles.…”
Section: Introductionmentioning
confidence: 99%